1999
DOI: 10.1021/jm990235p
|View full text |Cite
|
Sign up to set email alerts
|

Diethylcarbamoylating/Nitroxylating Agents as Dual Action Inhibitors of Aldehyde Dehydrogenase:  A Disulfiram−Cyanamide Merger

Abstract: Benzenesulfohydroxamic acid (Piloty's acid) was functionalized on the hydroxyl group with the N,N-diethylcarbamoyl group, and the hydroxylamine nitrogen was substituted with acetyl (1a), pivaloyl (1b), benzoyl (1c), and ethoxycarbonyl (1d) groups. Only compound 1d inhibited yeast aldehyde dehydrogenase (AlDH) in vitro (IC(50) 169 microM). When administered to rats, 1d significantly raised blood acetaldehyde levels following ethanol challenge, thus serving as a diethylcarbamoylating/nitroxylating, dual action i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…In a series of studies attempting to elucidate the mechanism of inhibition of AlDH by the hypoglycemic agent chlorpropamide, structure/activity examinations [92][93][94][95] suggested that sulfohydroxamic acids can be derivatized to give esterase-activated (compare DBHC, Scheme 2), as well as cytochrome P-450-acitvated, inhibitors of AlDH. In the case of the N-acylated, O-methylated sulfohydroxamic acids, O-demethylation by cytochrome P-450 gives rise to Nacylated sulfohydroxamic acids (Scheme 6; R groups shown are typical substituents, but not all combinations have been prepared).…”
Section: Scheme (3)mentioning
confidence: 99%
“…In a series of studies attempting to elucidate the mechanism of inhibition of AlDH by the hypoglycemic agent chlorpropamide, structure/activity examinations [92][93][94][95] suggested that sulfohydroxamic acids can be derivatized to give esterase-activated (compare DBHC, Scheme 2), as well as cytochrome P-450-acitvated, inhibitors of AlDH. In the case of the N-acylated, O-methylated sulfohydroxamic acids, O-demethylation by cytochrome P-450 gives rise to Nacylated sulfohydroxamic acids (Scheme 6; R groups shown are typical substituents, but not all combinations have been prepared).…”
Section: Scheme (3)mentioning
confidence: 99%
“…The choice of O-protecting groups, 14 particularly, acid-labile t-Bu, THP, and 2,4-dimethoxybenzyl 15 makes the subsequent automated high-throughput solid-phase synthesis a more robust process, as the protecting group can also be removed during the final cleavage from the solid support. Some of the known N,O-bisprotected hydroxylamine derivatives used for the synthesis of hydroxamates, including BOC-NH-OTHP, 16 BOC-NH-OTBDMS, 16 BOC-NH-OBn, 3,6 and O- (2,4)-dimethoxybenzyl-N- (2,4,6)-trimethoxybenzylhydroxylamine, 15 and certain previously reported Narylsulfonyl-O-substituted hydroxylamine derivatives, 17,18 suffer mainly from a lack of orthogonality of the N-and O-protecting groups during deprotection.…”
Section: Methodsmentioning
confidence: 99%
“…[5][6][7] In drug development, disulfide agents such as disulfiram exhibit unique pharmacological activities such as antialcoholic, and many other disulfides are used as antipoliovirus and antibacterial effects. [8][9][10] Interestingly, the S-S bond is employed for the delivery of drugs and release systems because of its ability to cleave upon an intracellular thiol-redox process. [11] Additionally, this important bond also substantially exists in natural products and food additives.…”
Section: Introductionmentioning
confidence: 99%